Translation of the play Heartbreak House and its stage production - Nikita S. Futljaev, Dmitry N. Zhatkin, (Opción, 2019)
The article analyzes the features of Aksenov’s translation of the play «Heartbreak House» by Shaw. We have used the comparative-historical, cultural-historical and comparative-typological methods of research, as well as elements of the socio-psychological method of reconstructing certain biographical realities. Translation of the play «Heartbreak House» by Aksenov in 1921, does not have the task of preserving the translational equivalence, as it is focused on recreating the antimilitarist spirit of the original. The later translations made the translation of Aksenov become a mere historical and cultural fact; its publication, carried out by us in 2015, was of purely academic significance.